Effect of two drafting modalities in cycling on running performance - Hausswirth, C.; Vallier, J. M.; Lehenaff, D.; Brisswalter, J.; Smith, D.; Millet, G.; Dreano, P. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The purposes of this study were first to compare the physiological responses during a triathlon where cycling was performed alternatively with another cyclist (alternate draft triathlon, ADT) or continuously behind him (continuous draft triathlon, CDT), and second to study the incidence of these two drafting modalities in cycling on the subsequent running performance done during a simulated triathlon. Methods: Ten male triathletes of national level performed a sprint distance triathlon (0.75-km swim, 20-km bike, 5-km run) on two different sessions, one where the triathlete alternatively rode in front or at the back of another cyclist and rotating every 500 m, the other where the triathlete drafted continuously a professional cyclist whose task was to reproduce all split times recorded during the alternate situation. Oxygen uptake (VO2), expiratory flow (VE), heart rate (HR) were recorded during the entire bike and run sections and blood lactate concentrations ([La-]b) were analyzed at the end of each event composing the triathlon. Results: The results showed that expiratory flow, oxygen uptake, heart rate and blood lactate concentrations were significantly lower in CDT on the bike compared with drafting in alternation (148.1 vs. 167.2 L.min-1, 49.9 vs. 59.8 mL.min-1.kg-1, 154.7 vs. 173.1 beats.min-1, 3.5 vs. 6.3 mmol.L-1, respectively). The results also revealed that running after biking in CDT (for similar cycling speeds) significantly improved the subsequent running speed compared to ADT (17.87 vs. 17.15 km.h-1). Furthermore, VE, VO2, HR, and [La-]b were significantly higher during CDT run compared with ADT run (175.6 vs. 170.4 L.min-1, 69.7 vs. 66.8 mL.min-1.kg-1, 182.6 vs. 177.3 beats.min-1, 9.6 vs. 7.5 mmol.L-1, respectively). Conclusions: These results showed that drafting continuously behind a lead cyclist allows triathletes to save a significant amount of energy during the bike leg of a sprint triathlon and creates the conditions for an improved running performance compared with a situation where cycling is performed alternating the lead with another cyclist.